Control of the olive moth, Prays oleae (Bern.), in organic olive groves - Bento, Albino (2009)
Olive tree is an important crop in Trás-os-Montes region (northeast of Portugal), where about 75 000 ha of surface are cultivated. In this region, 85% of the crop is conducted in traditional system. with low intensification and productivity, but with high quality of the olive oil produced. The organic production is one way to increase sustainability of this important agroecosystem. In this region, the olive surface certified in organic production has high potentiality of increasing. The olive moth, Prays oleae (Lep.: Plutellidae), which is one the most serious pests of olive trees in the Mediterranean basin, is the key pest of the crop in Trás-os-Montes region.